1986
DOI: 10.1073/pnas.83.1.53
|View full text |Cite
|
Sign up to set email alerts
|

An arachidonate metabolite is involved in the conversion from alpha 1- to beta-adrenergic glycogenolysis in isolated rat liver cells.

Abstract: In vitro incubation of isolated rat liver cells in a serum-free buffer leads to the suppression of the glycogenolytic effect of phenylephrine and the simultaneous emergence of a glycogenolytic response to isoproterenol within 4 hr. This time-dependent conversion of the adrenergic receptor response from a, to (3 type is prevented by the presence in the incubation medium of 0.5% fatty-acid-free, but not regular, bovine serum albumin. A 20-min exposure of freshly isolated liver cells to arachidonic acid (10 jzg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…The data represent mean k SE (bars) of values from three cultures in one typical experiment tablished. Evidence indicating post-receptor changes as mechanisms for the variations in P-adrenergic responsiveness in hepatocytes both in vivo and in vitro has been reported [18,19,[27][28][29][30]. It has been suggested that the increased Padrenoceptor density may be a consequence rather than a cause of the enhanced j-responsiveness in these cells [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data represent mean k SE (bars) of values from three cultures in one typical experiment tablished. Evidence indicating post-receptor changes as mechanisms for the variations in P-adrenergic responsiveness in hepatocytes both in vivo and in vitro has been reported [18,19,[27][28][29][30]. It has been suggested that the increased Padrenoceptor density may be a consequence rather than a cause of the enhanced j-responsiveness in these cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the changes in j3-receptor binding and P-response followed somewhat different time courses during the first hours in culture might suggest that post-receptor alterations are also involved. Kunos and coworkers [29,30] have recently shown that in vitro incubation of hepatocytes as suspensions leads to the suppression of the glycogenolytic effect of phenylephrine and the simultaneous emergence of a response to isoproterenol within 4 h and that a 20-min exposure of freshly isolated hepatocytes to arachidonic acid similarly caused a shift in the response from an a1 to a mixed al/P type. It is possible, however, that this effect was exerted at a level beyond the formation of CAMP, as an additional mechanism, since glycogen phosphorylase activity and not adenylate cyclase or production of CAMP was measured [29, 301. Our experiments with IAP treatment confirmed the reports by Ui and coworkers [27, 281 that Gi suppresses the j3-responsive adenylate cyclase, but, contrary to their data, our results did not support the idea that this suppression is a selective effect on the P-adrenoceptor-linked activity.…”
Section: Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The glycogenolytic response to circulating CATs arising from a treatment with PL may proceed through two distinct pathways, one represented by a cyclic AMP (cAMP)-dependent cascade mechanism, and the other by a cAMP-independent pathway triggered by changes in intracellular calcium (Erraji-Benchekroun et al 2005;Ishac and Kunos 1986;Kunos et al1984). While the formation of cAMP upon activation of adenylate cyclase is mediated by β 1 -and β 2 -adrenoceptors, the activation of the calcium-dependent pathway entails the participation of α 1 -adrenoceptors linked to phosphoinositide turnover.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the liver of adult male rats the glycogenolytic effect of CATs can proceed through a calciumlinked, cAMP-independent, α 1 -adrenergic mechanism. However, the same effect may take place by a predominantly β-adrenergic, cAMPdependent mechanism in the liver of female and fetal rats and in male rats in response to a variety of physiological (e.g., aging, fasting, liver regeneration), surgical (e.g., partial hepatectomy, adrenalectomy), pathological (e.g., glucocorticoid deficiency, malignant transformation, cholestasis, hypothyroidism) and experimental (e.g., animal species, incubation of the isolated cells in a serum-free medium) conditions (Erraji-Benchekroun et al 2005;Ishac and Kunos 1986;Kunos et al 1984).…”
Section: Discussionmentioning
confidence: 99%